Why has Latin America sped up ahead of the Philippines in economic and political reform? - Rosa Alonso i Terme (University of the Philippines, School of Economics (UPSE), 2015)
This paper compares trends in key economic, political and social development outcomes in the Philippines with those of Latin America, particularly since the 1990s. To do so, it uses standard indicators of development, including measures of institutional quality and good governance. The paper finds that Latin America is not only at a higher level of development, but has also made faster progress in most areas than the Philippines. This is especially the case as regards GDP per capita, poverty, education, health, infrastructure, social protection, right to life and security of the person and corruption. The Philippines, however, performs significantly better as regards gender and race and in some "niche" areas of ICT, including high-tech exports, while posting slightly higher ratings in government effectiveness. Both regions do well in the areas of macro-economic management and financial sector development. Overall performance as regards the quality of democracy is also roughly comparable. The paper argues that key policy drivers of the divergence include Latin America's: a) higher and better public spending; b) greater transparency and integrity in both the public and private sectors; and c) freer and more competitive markets.
Keywords: H11; O11; P16; P51; 330; public economics; development economics; political economy; economic systems